Solitary Fibrous Tumor of the Pleura: Surgical Treatment and Recurrence - Bove, Mary; Natale, Giovanni; Messina, Gaetana; Tiracorrendo, Matteo; Rendina, Erino Angelo; Fiorelli, Alfonso; D'Andrilli, Antonio (The Thoracic and Cardiovascular Surgeon, 2023)
Background Solitary fibrous tumors of the pleura (SFTPs) are primary pleural tumors originating from the mesenchymal tissue. Surgical treatment was the first choice for management of SFTPs. There were no defined guidelines for the follow-up of these tumors and the postoperative therapy due to the rarity of these tumors.Methods We conducted a retrospective, multicenter study from two high-volume centers in Italy. Data of patients diagnosed with pleural solitary fibrous tumors between January 2003 and October 2022 were prospectively recorded and retrospectively analyzed. The aim of this study was to identify predictive prognostic factors and the correlation between tumor characteristics and recurrence.Results In all, 107 patients undergoing R0 surgical resection of pleural solitary fibrous tumor were included in the study. Patients were divided in two groups: benign and malignant. All the patients were treated with surgery with the aim to obtain R0 resection. Lung resection was necessary when the tumor adhered strongly to the lung parenchyma or infiltrated it. Twenty of the 107 patients had tumor recurrence. At a multivariate analysis, histological characteristics (high mitotic index) and maximum standardized uptake values (maxSUV) were related to recurrence. The mean disease-free survival (DFS) was 143.3 ± 6.1 months.Conclusion In our experience, histological features of malignancy and maxSUV are significantly related to recurrence, which can occur even years after the first diagnosis. Surgical excision with negative surgical margins results in good long-term outcomes. After surgery, a long-term and strict follow-up should be done, in order to detect recurrence early. R0 of the recurrence is associated with long-term survival.
Keywords: thoracoscopy/VATS; surgery; complications; pleural disease (including drainage); chest